Mineral-filled low-BPA-content polycarbonate blend molding compounds and methods for production thereof
By optimizing component matching and production process in polycarbonate blend molding materials, the problem of increased thermal stress sensitivity and difficult control of free bisphenol A content of inorganic fillers is solved, and the multi-axis toughness and the reduction of free bisphenol A are achieved. Effects of bisphenol A content.
Patent Information
- Application Number
- CN202380047511.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-21
- Publication Date
- 2025-02-07
AI Technical Summary
When using inorganic fillers such as talc, existing polycarbonate blend molding materials can easily increase sensitivity to thermal stress, affecting mechanical properties and component surface quality. At the same time, the content of free bisphenol A is difficult to control, affecting environmental safety. .
Ensure component B and component C by combining appropriate components, including the selection of appropriate polycarbonates, thermoplastic polymers, non-thermoplastic polymers and inorganic fillers, and controlling the weight ratio and heat treatment conditions of components during the production process. The weight ratio of component B1 is at least 20%, and the content of free bisphenol A is reduced by a multi-step compounding method.
It improves the multi-axis toughness of the molding material, reduces the number of samples with brittle fracture, reduces the content of free bisphenol A, and improves mechanical properties and environmental friendliness.
Smart Images

Figure BDA0005190337550000081 
Figure BDA0005190337550000082 
Figure BDA0005190337550000321
Abstract
Description
[0001] The invention relates to a mineral-filled polycarbonate blend molding compound, a method for producing a mineral-filled polycarbonate blend molding compound, the use of the molding compound for producing moldings and moldings containing the molding compound.
[0002] Polycarbonate blend molding materials are already known. From these molding materials, moldings for a variety of applications are produced, for example for the automotive industry, the construction industry and the electronics industry. In most cases, the polycarbonate used is a polycarbonate containing structural units derived from bisphenol A. In the present invention, "containing structural units derived from bisphenol A" is understood to mean that bisphenol A is used as a diphenol component in the production of polycarbonates, optionally together with other diphenols. Thus, bisphenol A is covalently bonded to the polymer chain via carbonate groups, which are usually formed during the production of polycarbonates by polycondensation of hydroxyl groups in bisphenol A with carbonic acid halides or acyl halide groups or ester groups of carbonate esters.
[0003] By selecting the components of the composition and the amount range of these components in the composition, the properties of the molded articles made from such thermoplastic molding materials can be adapted to the requirements of the respective application. In order to increase the toughness, especially at low temperatures, blending partners with rubber-elastic properties are added to polycarbonate as impact modifiers.
[0004] Particularly in the field of automotive body parts applications and in two-component parts consisting of an opaque frame and a transparent or translucent window, attempts are increasingly being made to replace metals with plastics in order to reduce vehicle weight and thus fuel consumption, since automotive plastic parts are easy to produce by injection molding and offer greater design freedom and functional integration possibilities.
[0005] For horizontal automotive body parts with large surface areas, it is particularly important here that the moldings have low coefficients of thermal expansion for high dimensional stability and low warpage for small gap sizes as well as high material stiffness (high elastic modulus). In order to meet this requirement profile, mineral fillers such as talc are used as components of polycarbonate blend molding compounds in many cases. Inorganic pigments such as titanium dioxide can also be used to color the molding compounds.
[0006] EP 0 391 413 A2 discloses polymer compositions containing 40 to 80% by weight of aromatic polycarbonate, 5 to 50% by weight of a rubber-modified homopolymer or copolymer of a vinyl aromatic monomer (e.g. ABS) and 4 to 18% by weight of a platelet-shaped inorganic filler (e.g. talc), characterized by a reduced coefficient of thermal expansion, good low-temperature ductility, and high resistance to heat distortion.
[0007] EP 0 452 788 A2 discloses moldings produced from talc-filled PC / ABS compositions, which are characterized by a combination of good mechanical properties and reduced gloss. The composition contains 10 to 80 parts by weight of polycarbonate, 20 to 90 parts by weight of ABS and 2 to 25 parts by weight (based on a total of 100 parts by weight of polycarbonate and ABS) of talc having a median particle size of 1.5 to 20 μm. Molding compounds are produced from these compositions by a single-step compounding process.
[0008] WO 98 / 51737 A1 discloses a thermoplastic polymer composition having improved properties, for example in terms of heat distortion resistance, melt flow, low temperature impact toughness and dimensional stability, which contains 65 to 85% by weight of an aromatic polycarbonate, 10 to 50% by weight of a rubber-modified copolymer (e.g. ABS) and 1 to 15% by weight of a particulate mineral filler (e.g. talc) having an average maximum characteristic size of 0.1 to 30 μm. This application also discloses only the production of thermoplastic molding compounds by a single-step compounding process.
[0009] However, the use of inorganic fillers such as talc or titanium dioxide in polycarbonate blend molding compounds leads to an increased sensitivity to thermal stresses, since, for example, the filler base induces a decrease in the molecular weight of the polycarbonate. In order to avoid this effect, which ultimately has an adverse effect on the mechanical properties and the surface quality of the components, it is advantageous to stabilize the molding compound. Suitable for this purpose include, for example, Bronsted acidic compounds, which are added to the molding compound during compounding.
[0010] WO 2013 / 060687 A1 discloses polycarbonate compositions stabilized with Bronsted acidic compounds, which have improved thermal processing stability and contain optionally rubber-modified vinyl (co)polymers and also optionally talc, which are produced by a special process in which the Bronsted acidic compounds are applied to an inorganic or organic adsorbent or absorbent, preferably finely divided silica, before compounding. The disclosed thermally stable polycarbonate compositions are produced by a single-step compounding process. Mechanical powder mixtures of pulverulent formulation components can be used here.
[0011] Polycarbonate molding compounds and molded articles made from them usually contain small amounts of free (i.e. chemically unbound) bisphenol A (BPA). However, efforts are underway to impose strict regulatory limits on the free BPA content in molding compounds and articles in order to minimize the impact of BPA on the environment. For example, the corresponding agencies in the European Union are preparing for this.
[0012] It has been found that inorganic fillers as components of polycarbonate moulding materials can lead to an increased free BPA content, especially at high processing temperatures and long residence times in the melt, and therefore the production and processing of such moulding materials also requires particular care from this point of view.
[0013] Inorganic fillers can further lead to a deterioration in the mechanical data of moldings made from polycarbonate molding compounds. In particular, the toughness under multiaxial stress (as measured, for example, in a puncture test) can be adversely affected.
[0014] Therefore, it is necessary to provide mineral-filled polycarbonate blend molding compounds with improved multiaxial toughness. Preferably, the maximum force and the total energy should be increased and the number of specimens that fail by splintering (brittle fracture) should be reduced. The latter is very important for safety-related applications such as the automotive sector.
[0015] It would further be desirable to provide a method for producing mineral-filled polycarbonate blend molding compounds having a reduced BPA content.
[0016] WO 2008 / 122359 A1 discloses talc-filled PC / ABS compositions and molding compounds made therefrom, which are stabilized against polycarbonate degradation by the addition of Bronsted acids and thus have improved thermal stability during compounding and molding. The application is silent on the effect of Bronsted acids on the free BPA content in such molding compounds and moldings made therefrom.
[0017] WO 99 / 28386 A1 discloses a molding compound comprising at least one aromatic or partially aromatic polyester and at least one polycarbonate, at least one graft copolymer, at least one copolymer containing vinyl aromatic monomers, at least one filler and at least one low molecular weight halogen-free acid. Polyacrylates, flame retardants and polymer additives are also disclosed in these molding compounds as other optional components. The molding compound is characterized by improved mechanical properties (elongation at break) and improved melt flowability. The molding compound is preferably produced by mixing all components by coextrusion at a temperature of 200° C. to 320° C., i.e. in a single-step compounding process. The application also discloses that the individual components can be premixed. However, the application does not mention the technical effects that can be achieved by premixing the individual components, as well as which components of the composition are advantageously premixed and in what manner and type and under what conditions such premixing is carried out.
[0018] WO 2018 / 037037 A1 discloses a composition obtained by mixing at least components A) to C), wherein A) is a polycarbonate, B) is an unsized talc, and C) at least one having an acid value of at least 30 mg KOH / g and an average molecular weight M wThe invention relates to an anhydride-modified α-olefin polymer of 4000 to 40000 g / mol, wherein the amounts of B) and C) are matched to each other before mixing so that 0.10 to 1.4 parts by weight of component C) are used per 10 parts by weight of component B), and wherein the composition does not contain polyester and graft polymer. In these compositions, the polycarbonate has improved stability against decomposition. In the production of the composition, the sizing of the talc B) with the anhydride-modified α-olefin polymer C) is carried out in situ during the mixing of the talc B) with the polycarbonate A) in the form of a melt, i.e. the polycarbonate A) is at least partially, but in a preferred embodiment already completely, present in the form of a melt during the mixing of the talc B) with the α-olefin polymer C).
[0019] US 2006 / 0287422 A1 discloses a thermoplastic polycarbonate composition comprising a mineral filler and preferably an inorganic acid or an acid salt of a preferably inorganic acid and optionally an impact modifier and / or a vinyl (co)polymer, wherein the filler and the acid or acid salt are used in a specific ratio. The molding compound made from such a composition has improved mechanical properties and improved thermal stability of the polycarbonate to molecular weight degradation. The examples disclosed in the application are all produced in a twin-screw extruder in a single-step compounding method disclosed as being preferred.
[0020] The described prior art has not provided adequate solutions to the above mentioned problems.
[0021] However, it has now been found that at least one of the above problems is solved by a thermoplastic molding compound comprising:
[0022] A) at least one polycarbonate and / or polyester carbonate, each of which contains structural units derived from bisphenol A,
[0023] B) other polymers different from component A or a mixture consisting of polymers each different from component A,
[0024] Component B consists of the following
[0025] B1) at least one thermoplastic polymer and
[0026] Optionally B2) at least one non-thermoplastic polymer,
[0027] C) at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica, and combinations of said fillers, wherein component C preferably contains talc, and
[0028] D) optionally at least one non-polymeric polymer additive and / or at least one non-polymeric processing aid, each of which is different from component C,
[0029] The weight ratio of component B to component C is at least 0.5, preferably at least 1, particularly preferably at least 1.3,
[0030] wherein the weight proportion of component B1 in component B is at least 20%, preferably at least 50%, more preferably at least 70% by weight,
[0031] The mass proportion of free bisphenol A in the molding compound is less than 30 ppm, preferably less than 20 ppm, and particularly preferably less than 10 ppm.
[0032] The polycarbonates and polyester carbonates used as component A in the context of the present invention are also referred to hereinafter synonymously as aromatic polycarbonates or aromatic polyester carbonates.
[0033] Component B is preferably selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more of each of these polymers, and is particularly preferably selected from rubber-free vinyl (co)polymers and rubber-modified vinyl (co)polymers and mixtures of one or more of each of these polymers.
[0034] The molding compound preferably comprises
[0035] 30% to 85% by weight, more preferably 40% to 80% by weight, particularly preferably 45% to 75% by weight of component A,
[0036] 2% to 50% by weight, more preferably 7% to 40% by weight, particularly preferably 15% to 35% by weight, of component B,
[0037] 3 to 40% by weight, more preferably 5 to 30% by weight, particularly preferably 8 to 25% by weight, of component C,
[0038] 0% to 10% by weight, more preferably 0.1% to 5% by weight, particularly preferably 0.2% to 3% by weight, of component D.
[0039] The stated % by weight data are based on the total weight of the thermoplastic molding compound.
[0040] The weight ratio of component B to component C is preferably 0.5 to 5, preferably 1 to 3, particularly preferably 1.3 to 2.
[0041] In a further preferred embodiment, at least 90%, more preferably at least 95%, most preferably 100% of the molding compound consists of components A, B, C and D.
[0042] Likewise, it has been found that a molding compound having the desired properties is obtained by a method for producing a thermoplastic molding compound, the method comprising the steps of
[0043] (i) The masterbatch is produced by melt compounding the following components in an internal kneader or a co-kneader:
[0044] B) a polymer other than a polycarbonate containing structural units derived from bisphenol A and other than a polyester carbonate containing structural units derived from bisphenol A, or a mixture of polymers other than a polycarbonate containing structural units derived from bisphenol A and other than a polyester carbonate containing structural units derived from bisphenol A,
[0045] Component B consists of the following
[0046] B1) at least one thermoplastic polymer and
[0047] optionally B2) at least one non-thermoplastic polymer,
[0048] C) at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica, and combinations of said fillers, wherein component C preferably contains talc, and
[0049] D) optionally at least one non-polymeric polymer additive and / or at least one non-polymeric processing aid, each of which is different from component C,
[0050] The weight ratio of component B to component C is at least 0.5, preferably at least 1, particularly preferably at least 1.3,
[0051] and
[0052] wherein the weight proportion of component B1 in component B is at least 50%, preferably at least 60% by weight, more preferably at least 70% by weight, and
[0053] (ii) melt compounding the masterbatch obtained in step (i) with at least one polycarbonate and / or polyester carbonate as component A and optionally further proportions of components B, C and / or D and / or the total amount of component D, the polycarbonate and / or polyester carbonate each containing structural units derived from bisphenol A.
[0054] The weight ratio of component B to component C in the method of the present invention is preferably 0.5 to 5, more preferably 1 to 3, particularly preferably 1.3 to 2.
[0055] Component B is preferably selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more of these polymers, and is particularly preferably selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers and mixtures of one or more of these polymers.
[0056] It is also possible in the process of the invention to use only a portion of the total amount of component B and / or component C and / or component D in step (i). In this case, the remaining amount of component B and / or component C and / or component D is used in step (ii). It is also possible that component D is used completely in step (ii).
[0057] Preferably, in step (i), at least 80% by weight, more preferably at least 90% by weight, particularly preferably at least 95% by weight of the total amount of component C is used. Most preferably, the total amount of component C is used in step (i).
[0058] Step (ii) is preferably carried out in a compounding apparatus selected from a single screw extruder, a co-rotating or counter-rotating twin screw extruder, a planetary roller extruder, an internal kneader or a co-kneader. A co-kneader is a continuously operated kneader. An internal kneader is usually operated in an intermittent mode, i.e. discontinuously.
[0059] The co-kneader is preferably operated in such a way that a rotation and an axial back-and-forth movement of the mixing and kneading screw shaft are achieved simultaneously. The oscillating screw shaft ensures an intensive product exchange in the axial direction.
[0060] Steps (i) and (ii) are carried out in a temperature range of 200° C. to 350° C., with a residence time of the components in melt form of 15 seconds to 5 minutes.
[0061] Process step (i) is particularly preferably carried out in a co-kneader. When process step (i) is carried out in a co-kneader, step (i) is preferably carried out at a melt temperature of 210° C. to 260° C., more preferably 215° C. to 250° C., particularly preferably 220° C. to 240° C. When process step (i) is carried out in a co-kneader, the residence time of the components in melt form in step (i) is preferably 1 to 5 minutes, more preferably 1.5 to 4 minutes, particularly preferably 2 to 3.5 minutes.
[0062] Particularly preferably, process step (ii) is carried out in a twin-screw extruder. When process step (ii) is carried out in a twin-screw extruder, step (ii) is preferably carried out at a melt temperature of 260° C. to 320° C. When process step (ii) is carried out in a twin-screw extruder, the residence time of the components in melt form in step (ii) is preferably 15 to 60 seconds.
[0063] In a particularly preferred process, step (i) is carried out in a co-kneader at a melt temperature of 210° C. to 260° C., with a residence time of the components in the melt of 1 to 5 minutes, and step (ii) is carried out in a twin-screw extruder at a melt temperature of 260° C. to 320° C., with a residence time of the components in the melt of 15 to 60 seconds.
[0064] In both step (i) and step (ii), the composition can be degassed by applying negative pressure. The absolute pressure established is preferably not more than 400 mbar, more preferably not more than 300 mbar, particularly preferably not more than 200 mbar. Degassing is preferably carried out in step (ii).
[0065] The preferred ranges for the ratios of components A, B, C and D mentioned for the molding material also apply to the process of the invention. In this case, these ratios are based on the total amount used, regardless of whether partial amounts of components B and D are used in step (i) or their total amount has already been used.
[0066] Component A
[0067] Polycarbonates and / or polyester carbonates of component A which are suitable according to the invention are known from the literature or can be prepared by methods known from the literature (for the preparation of polycarbonates, see, for example, Schnell, "Chemistry and Physics of Polycarbonates", Interscience Publishers, 1964 and DE-AS 1 495 626, DE-A 2 232 877, DE-A 2 703 376, DE-A 2 714 544, DE-A 3 000 610, DE-A 3 832 396; for the production of polyester carbonates, for example DE-A 3 007 934).
[0068] The polycarbonates suitable for use as component A according to the invention are produced, for example, by reaction of bisphenol A and optionally other diphenols with carbonic acid halides (preferably phosgene) and / or with aromatic dicarboxylic acid halides (preferably phthaloyl halides) by the phase interface process, with the optional use of chain terminators (for example monophenols) and optionally trifunctional or more than trifunctional branching agents (for example trisphenols or tetraphenols). The production can likewise be carried out by the melt polymerization process by reaction of bisphenol A and optionally other diphenols with, for example, diphenyl carbonate.
[0069] In addition to bisphenol A, diphenols suitable for producing polycarbonates suitable according to the invention as component A and / or suitable for producing polyester carbonates suitable according to the invention as component A preferably include those of the formula (I):
[0070]
[0071] in
[0072] A is a single bond, a C1 to C5 alkylene group, a C2 to C5 alkylidene group, a C5 to C6 cycloalkylidene group, -O-, -SO-, -CO-, -S-, -SO2-, a C6 to C6 alkylene group to which another aromatic ring optionally containing heteroatoms may be fused. 12 Arylene,
[0073] or a group of formula (II) or (III)
[0074]
[0075] B represents C1 to C 12 alkyl, preferably methyl, halogen, preferably chlorine and / or bromine,
[0076] x is in each case independently of one another 0, 1 or 2,
[0077] p is 1 or 0, and
[0078] R 5 and R 6 For each X 1 are selected individually and independently of one another to be hydrogen or C1 to C6 alkyl, preferably hydrogen, methyl or ethyl,
[0079] X 1 is carbon, and
[0080] m is an integer from 4 to 7, preferably 4 or 5, provided that at least one atom X 1 Upper, R 5 and R 6 All are alkyl.
[0081] In addition to bisphenol A, diphenols that are preferably used include hydroquinone, resorcinol, dihydroxybiphenols, bis(hydroxyphenyl)C1-C5 alkanes, bis(hydroxyphenyl)C5-C6 cycloalkanes, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)sulfoxides, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfones and α,α-bis(hydroxyphenyl)diisopropylbenzene and their ring-brominated and / or ring-chlorinated derivatives.
[0082] Particularly preferred further diphenols are 4,4′-dihydroxybiphenyl, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4′-dihydroxydiphenyl sulfide, 4,4′-dihydroxydiphenyl sulfone, and their dibrominated and tetrabrominated or chlorinated derivatives, for example 2,2-bis(3-chloro-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane or 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane.
[0083] These diphenols can be used individually or in the form of any desired mixtures. These diphenols are known from the literature or can be obtained by methods known from the literature.
[0084] The polycarbonates used according to the invention preferably contain at least 20% by weight, more preferably at least 50% by weight, particularly preferably at least 80% by weight and most preferably 100% by weight of structural units derived from bisphenol A, based in each case on the sum of all structural units derived from bisphenols.
[0085] Examples of chain terminators suitable for the production of polycarbonates include phenol, p-chlorophenol, p-tert-butylphenol or 2,4,6-tribromophenol, and long-chain alkylphenols, for example 4-[2-(2,4,4-trimethylpentyl)]phenol, 4-(1,3-tetramethylbutyl)phenol according to DE-A 2 842005, or mono- or dialkylphenols having a total of 8 to 20 carbon atoms in the alkyl substituent, for example 3,5-di-tert-butylphenol, p-isooctylphenol, p-tert-octylphenol, p-dodecylphenol and 2-(3,5-dimethylheptyl)phenol and 4-(3,5-dimethylheptyl)phenol. The chain terminators which can be used are generally in an amount of 0.5 mol % to 10 mol %, based on the total number of moles of the diphenols used in each case.
[0086] The average molecular weight (weight average Mw) of the thermoplastic aromatic polycarbonate is preferably 20000 to 40000 g / mol, more preferably 24000 to 32000 g / mol, particularly preferably 26000 to 30000 g / mol, measured by GPC (gel permeation chromatography), using dichloromethane as solvent, calibrated with linear polycarbonates (composed of bisphenol A and phosgene) of known molar mass distribution from PSS Polymer Standards Service GmbH, Germany, and calibrated according to method 2301-0257502-09D (German version 2009) of Currenta GmbH & Co. OHG, Leverkusen. The eluent is dichloromethane. Column combination of crosslinked styrene-divinylbenzene resin. Analytical column diameter: 7.5 mm; length: 300 mm. Column material particle size: 3 μm to 20 μm. Solution concentration: 0.2% by weight. Flow rate: 1.0 ml / min, solution temperature: 30°C. UV and / or RI detection is used.By means of the preferred ranges, a particularly advantageous balance of mechanical and rheological properties of the composition of the invention is achieved.
[0087] The polycarbonates can be branched in a known manner, more preferably by adding 0.05 to 2.0 mol % of trifunctional or more than trifunctional compounds, for example compounds with three or more phenolic groups, based on the total amount of diphenols used. Preference is given to using linear polycarbonates, which are more preferably based on bisphenol A.
[0088] Both homopolycarbonates and copolycarbonates are suitable. For the preparation of the copolycarbonates of component A of the present invention, 1 to 25% by weight, preferably 2.5 to 25% by weight, of polydiorganosiloxanes with hydroxyaryloxy end groups, based on the total amount of diphenols used, can also be used. These are known (US 3 419 634) and can be prepared by methods known in the literature. Also suitable are copolycarbonates containing polydiorganosiloxanes, the preparation of which is described, for example, in DE-A 3 334 782.
[0089] Aromatic dicarboxylic acid dihalides used for producing polyester carbonates are preferably dichlorides of isophthalic acid, terephthalic acid, diphenyl ether 4,4'-dicarboxylic acid and naphthalene-2,6-dicarboxylic acid. Particularly preferred are mixtures of dichlorides of isophthalic acid and terephthalic acid in a ratio of 1:20 to 20:1.
[0090] In the production of polyester carbonates, a carbonic acid halide, preferably phosgene, is also co-used as difunctional acid derivative.
[0091] In addition to the above-mentioned monophenols, chain terminators which come into consideration for the production of polyester carbonates include their chlorocarbonates and the acid chlorides of aromatic monocarboxylic acids, which may optionally be replaced by C1 to C 22Alkyl or halogen atom substituted, and aliphatic C2 to C 22 Monocarboxylic acid chlorides.
[0092] The amount of chain terminators is in each case from 0.1 to 10 mol %, based on the moles of diphenol for phenolic chain terminators and on the moles of dicarboxylic acid dichloride for monocarboxylic acid chloride chain terminators.
[0093] In the production of the polyester carbonates it is also possible to use one or more aromatic hydroxycarboxylic acids.
[0094] The polyester carbonates may be linear or branched in a known manner (cf. DE-A 2940024 and DE-A 3007934), with linear polyester carbonates being preferred.
[0095] Useful branching agents include, for example, tri- or polyfunctional carboxylic acid chlorides, such as trimesoyl chloride, cyanuric chloride, 3,3′,4,4′-benzophenonetetracarboxylic acid chloride, 1,4,5,8-naphthalenetetracarboxylic acid chloride or pyromellitic acid chloride in an amount of 0.01 to 1.0 mol %, based on the dicarboxylic acid dichloride used, or tri- or polyfunctional phenols, such as phloroglucinol, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)hept-2-ene, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)heptane, 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)benzene, The branching agents used are 0.01 to 1.0 mol % based on the diphenols used. The phenolic branching agents can be pre-charged with the diphenols; and the acid chloride branching agents can be introduced with the diacyl chlorides.
[0096] The proportion of carbonate structural units in polyester carbonates can be changed arbitrarily. The proportion of carbonate groups is preferably at most 90 mol%, in particular at most 80 mol%, and particularly preferably at most 50 mol%, based on the sum of ester groups and carbonate groups. Both the ester part and the carbonate part in polyester carbonate can exist in block form or in a randomly distributed form in the polycondensate.
[0097] The polycarbonates and polyester carbonates can be used alone or in any desired mixtures.
[0098] Preference is given to using as component A linear polycarbonates based exclusively on bisphenol A.
[0099] Component B
[0100] As component B, the molding compound according to the invention contains at least one further polymer different from component A or a mixture of polymers each different from component A.
[0101] Component B consists of the following
[0102] B1) at least one thermoplastic polymer and
[0103] Optionally B2) at least one non-thermoplastic polymer
[0104] And the weight proportion of component B1 in component B is at least 20 weight %, preferably at least 50 weight %, more preferably at least 70 weight %.
[0105] A mixture of polymers may mean that the corresponding granules or powders made of the polymers are distributed as evenly as possible in one another. This can be achieved by filling the granules or powders into a suitable mixing device or container and mixing them, for example, by shaking or stirring at room temperature, elevated temperature or alternatively also under cooling, without having to melt one or more polymers.
[0106] A mixture of polymers may also mean a compound (polymer blend) obtained by melting one or more polymers by introducing thermal or mechanical energy and mixing the polymers in the melt. Melting and mixing can be carried out, for example, in an extruder or a kneader.
[0107] Many commercially available thermoplastic processable materials are mixtures of thermoplastic and non-thermoplastic polymers obtained by melt compounding. This is the case, for example, with many commercially available ABS (acrylonitrile-butadiene-styrene) plastics for injection molding or extrusion applications, which are typically obtained industrially by compounding a thermoplastic styrene-acrylonitrile copolymer (SAN) with a non-thermoplastic emulsion ABS graft polymer.
[0108] Component B is preferably selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, polyolefins, polyamides, polyesters, polycarbonates different from component A and high-temperature polymers, such as polysulfones, polyimides, polyphenylenes, polyaromatics, polyether ketones, polyphenylene sulfides and mixtures of one or more of such polymers in each case, more preferably selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more of such polymers in each case, most preferably selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers and mixtures of one or more of such polymers in each case.
[0109] The polyolefins which can be used as component B are prepared by chain polymerization, preferably by free radical polymerization. The monomers used include olefins. Another name for olefins is olefins. The monomers can be polymerized individually or as a mixture of various monomers.
[0110] Preferred monomers are ethylene, propylene, 1-butene, isobutylene, 1-pentene, 1-heptene, 1-octene and 4-methyl-1-pentene.
[0111] The polyolefin may contain up to 50% by weight, more preferably up to 30% by weight, of vinyl comonomers such as methyl acrylate, ethyl acrylate, butyl acrylate and methyl methacrylate.
[0112] Polyolefins are semi-crystalline or amorphous and may be linear or branched. The production of polyolefins has long been known to those skilled in the art.
[0113] The polymerization can be carried out, for example, at a pressure of 1 to 3000 bar and a temperature of 20° C. to 300° C., optionally using a catalyst system. Examples of suitable catalysts include mixtures of titanium and aluminum compounds and metallocenes.
[0114] By changing the polymerization conditions and the catalyst system, the number of branches, crystallinity and density of the polyolefin can be varied within a wide range. These measures are also well known to those skilled in the art.
[0115] Component B or ingredients of component B that can be used also include rubber-modified vinyl (co)polymers or rubber-free vinyl (co)polymers or mixtures of a plurality of such polymers.
[0116] The rubber-modified vinyl (co)polymers are preferably rubber-modified graft polymers. Depending on the rubber content, they can be thermoplastic (according to component B1) or non-thermoplastic (according to component B2). Usually, rubber-modified graft polymers with a rubber content of more than 40% are usually no longer thermoplastically processable alone, i.e. without the addition of other polymers, for example other subcomponents B that are thermoplastically processable, for example rubber-free or low-rubber subcomponents B.
[0117] If in process step (i) a pre-compound of at least one thermoplastic polymer according to component B1 and at least one non-thermoplastic polymer according to component B2 is used as component B or as part of component B, for example a pre-compound of one or more rubber-free or low-rubber vinyl (co)polymers with one or more rubber-modified graft polymers, wherein the rubber content is each greater than 40% by weight, then when calculating the weight proportion of component B1 in component B in the composition of the present invention, only the corresponding amount proportion of B1 in the pre-compound as a thermoplastic polymer B1 should be taken into account, even if the pre-compound is itself thermoplastic.
[0118] The rubber-modified graft polymer can, for example, have a core-shell structure. Such rubber-modified graft polymers having a core-shell structure are usually prepared by emulsion polymerization and usually have a rubber content of 20 to 90% by weight, preferably 30 to 85% by weight, and more preferably 40 to 80% by weight. Due to the high rubber content, such rubber-modified graft polymers having a core-shell structure, especially those having a rubber content of more than 40%, are usually not thermoplastic enough to be processed well, and are generally not suitable as the only component B in the production of the masterbatch in the process step (i) of the present invention in the context of the present invention. However, as a component of component B, they can be used in the production of the masterbatch in a mass proportion of up to 50% by weight, preferably up to 40% by weight, and more preferably up to 30% by weight, in each case based on component B. If a higher amount (based on component B) than the amount of the rubber-modified graft polymer having a core-shell structure described above should be used in the polycarbonate blend composition of the present invention, these additional amounts can be added in the process step (ii) of the production process of the present invention.
[0119] Other suitable rubber-modified graft polymers according to the invention are those which, as a result of production, contain a dispersed phase embedded in a vinyl (co)polymer matrix, the dispersed phase consisting of rubber particles grafted with a vinyl (co)polymer, the rubber particles containing vinyl (co)polymer inclusions. Such rubber-modified graft polymers can be obtained by bulk polymerization.
[0120] The rubber modified vinyl (co)polymer used as component B comprises
[0121] 5 to 95, preferably 15 to 92, in particular 20 to 60% by weight of at least one vinyl monomer as graft coating (graft shell), based on the rubber-modified vinyl (co)polymer, which is grafted onto
[0122] Based on 95 to 5, preferably 85 to 8, and especially 80 to 40% by weight of one or more rubbery graft bases of the rubber-modified vinyl (co)polymer, the glass transition temperature is preferably <10°C, more preferably <0°C, and particularly preferably <-20°C.
[0123] The glass transition temperature is measured in accordance with DIN EN 61006 using dynamic differential calorimetry (DSC) at a heating rate of 10 K / min, with Tg being defined as the midpoint temperature (tangent method).
[0124] The median particle size of the grafted base (d 50 ) is usually 0.05 to 10 μm, preferably 0.1 to 5 μm, particularly preferably 0.2 to 1 μm.
[0125] Median particle size d s0It is the diameter above and below which 50% by weight of the particles exist, respectively. It can be determined by ultracentrifugation measurement (W. Scholtan, H. Lange, Kolloid, Z. and Z. Polymere 250 (1972), 782-1796).
[0126] The vinyl monomers used to produce the rubber modified vinyl (co)polymers are preferably a mixture of the following
[0127] 50 to 99, preferably 60 to 80, in particular 70 to 80 parts by weight, based on the graft coating, of vinyl aromatics and / or ring-substituted vinyl aromatics (e.g. styrene, α-methylstyrene, p-methylstyrene, p-chlorostyrene) and / or (C1-C8) alkyl methacrylates, such as methyl methacrylate, ethyl methacrylate), preferably at least one selected from the monomers styrene, α-methylstyrene and methyl methacrylate, particularly preferably styrene, and
[0128] 1 to 50, preferably 20 to 40, in particular 20 to 30 parts by weight of vinyl cyanide (unsaturated nitriles, such as acrylonitrile and methacrylonitrile) and / or (C1-C8)alkyl (meth)acrylates, such as methyl methacrylate, n-butyl acrylate, tert-butyl acrylate and / or derivatives of unsaturated carboxylic acids (such as anhydrides and imides), such as maleic anhydride and N-phenylmaleimide, preferably at least one selected from the monomers acrylonitrile, maleic anhydride and methyl methacrylate, particularly preferably acrylonitrile, based on the graft coating.
[0129] In another preferred embodiment, the graft coating consists of methyl methacrylate.
[0130] Suitable graft bases for rubber-modified vinyl (co)polymers are, for example, diene rubbers, EP(D)M rubbers (i.e. rubbers based on ethylene / propylene and optionally dienes), acrylates, polyurethanes, silicones, chloroprene and ethylene / vinyl acetate rubbers and silicone / acrylate composite rubbers.
[0131] Preferred graft bases are diene rubbers, for example based on butadiene and isoprene, or mixtures of diene rubbers or copolymers of diene rubbers or mixtures thereof with other copolymerizable monomers, such as vinyl polymers also used for the graft coating.
[0132] A particularly preferred graft base is pure polybutadiene rubber.
[0133] Particularly preferred rubber-modified vinyl (co)polymers are, for example, ABS or MBS polymers, as described in DE-A 2035390 (= US-PS 3644574) or DE-OS 2248242 (= GB-B 1 409 275) or Ullmanns der Technischen Chemie, Vol. 19 (1980), p. 280 ff.
[0134] The rubber-modified vinyl (co)polymers are prepared by free radical polymerization, for example by emulsion, suspension, solution or bulk polymerization, preferably by emulsion or bulk polymerization.
[0135] The gel fraction of the graft base is at least 30% by weight, preferably at least 40% by weight and in particular at least 60% by weight, measured as the insoluble fraction in toluene.
[0136] The gel content of the graft base is determined at 25° C. in suitable solvents as the proportion of the graft base which is insoluble in these solvents (M. Hoffmann, H. R.Kuhn, Polymeranalytik Iund II, Georg Thieme-Verlag, Stuttgart 1977).
[0137] Particularly suitable graft rubbers are also ABS polymers which are prepared according to US Pat. No. 4,937,285 by redox initiation with an initiator system consisting of an organic hydroperoxide and ascorbic acid.
[0138] Since it is well known that the grafting monomers are not necessarily completely grafted onto the grafting base in the grafting reaction, the graft polymers according to the invention are also to be understood as products produced by (co)polymerization of the grafting monomers in the presence of the grafting base and obtained together in the post-processing. Therefore, these products can also contain free (co)polymers of the grafting monomers, i.e., not chemically bound to the rubber.
[0139] Acrylate rubbers suitable for use as graft bases are preferably polymers of alkyl acrylates, optionally with up to 40% by weight, based on the graft base, of other polymerizable ethylenically unsaturated monomers. Preferred polymerizable acrylates include C1- to C8-alkyl esters, such as methyl, ethyl, butyl, n-octyl and 2-ethylhexyl esters; haloalkyl esters, preferably halo-C1-C8-alkyl esters, such as chloroethyl acrylate, and mixtures of these monomers.
[0140] Further suitable grafting bases are silicone rubbers having grafting-active sites, as described, for example, in DE-OS 3 704 657, DE-OS 3 704 655, DE-OS 3 631 540 and DE-OS 3 631 539.
[0141] The rubber-free vinyl (co)polymer is preferably a rubber-free homopolymer and / or copolymer of at least one monomer selected from vinyl aromatics, vinyl cyanides (unsaturated nitriles), (meth)acrylate (C1 to C8) alkyl esters, unsaturated carboxylic acids and derivatives of unsaturated carboxylic acids (such as anhydrides and imides).
[0142] Particularly suitable are rubber-free vinyl (co)polymers of the following composition:
[0143] 50 to 99% by weight, preferably 60 to 80% by weight, in particular 70 to 80% by weight, based in each case on the total weight of the rubber-free vinyl (co)polymer, of at least one monomer selected from vinyl aromatics, for example styrene, α-methylstyrene, vinyl aromatics substituted on the ring, for example p-methylstyrene, p-chlorostyrene and (C1-C8)alkyl (meth)acrylates, for example methyl methacrylate, n-butyl acrylate, tert-butyl acrylate, and
[0144] 1 to 50% by weight, preferably 20 to 40% by weight and in particular 20 to 30% by weight, based in each case on the total weight of the rubber-free vinyl (co)polymer, of at least one monomer selected from vinyl cyanides, for example unsaturated nitriles such as acrylonitrile and methacrylonitrile, (C1-C8)alkyl (meth)acrylates, for example methyl methacrylate, n-butyl acrylate and tert-butyl acrylate, unsaturated carboxylic acids and derivatives of unsaturated carboxylic acids, for example maleic anhydride and N-phenylmaleimide.
[0145] These rubber-free vinyl (co)polymers are resinous and thermoplastic. Particularly preferred are copolymers of styrene and acrylonitrile.
[0146] Such rubber-free vinyl (co)polymers are known and can be prepared by free radical polymerization, in particular by emulsion, suspension, solution or bulk polymerization. The average molecular weight Mw (weight average, measured by GPC with polystyrene standards) of the rubber-free vinyl (co)polymers is preferably from 15000 to 250000 g / mol, preferably from 80000 to 150000 g / mol.
[0147] In a preferred embodiment, aromatic polyesters that come into consideration as component B are polyalkylene terephthalates. In a particularly preferred embodiment, they are reaction products of aromatic dicarboxylic acids or their reactive derivatives (e.g. dimethyl esters or anhydrides) with aliphatic, cycloaliphatic or araliphatic diols and mixtures of these reaction products. Particularly preferred aromatic polyalkylene terephthalates contain at least 80% by weight, preferably at least 90% by weight, of terephthalic acid groups, based on the dicarboxylic acid component, and at least 80% by weight, preferably at least 90% by weight, of ethylene glycol groups and / or butane-1,4-diol groups, based on the diol component.
[0148] In addition to terephthalic acid groups, the preferred aromatic polyalkylene terephthalates may also comprise up to 20 mol %, preferably up to 10 mol %, of other aromatic or cycloaliphatic dicarboxylic acid groups having 8 to 14 carbon atoms or aliphatic dicarboxylic acid groups having 4 to 12 carbon atoms, for example groups of phthalic acid, isophthalic acid, naphthalene-2,6-dicarboxylic acid, 4,4′-biphenyldicarboxylic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, cyclohexanediacetic acid.
[0149] In addition to ethylene glycol and / or butane-1,4-diol groups, the preferred aromatic polyalkylene terephthalates may contain up to 20 mol %, preferably up to 10 mol %, of other aliphatic diols having 3 to 12 carbon atoms or cycloaliphatic diols having 6 to 21 carbon atoms, for example propane-1,3-diol, 2-ethylpropane-1,3-diol, neopentyl glycol, pentane-1,5-diol, hexane-1,6-diol, cyclohexane-1,4-dimethanol, 3-ethylpentane-2,4-diol, 2-methyl ... The radicals of DE-A 2 407 674, 2 407 776, 2 715 932 include 2,4-di(β-hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(4-β-hydroxyethoxyphenyl)propane and 2,2-bis(4-hydroxypropoxyphenyl)propane.
[0150] Aromatic polyalkylene terephthalates can be branched by adding relatively small amounts of trihydric or tetrahydric alcohols or trihydric or tetrahydric carboxylic acids, for example according to DE-A 1 900 270 and US Pat. No. 3 692 744. Examples of preferred branching agents are trimesic acid, trimellitic acid, trimethylolethane and trimethylolpropane and also pentaerythritol.
[0151] Particular preference is given to aromatic polyalkylene terephthalates which are prepared exclusively from terephthalic acid and its reactive derivatives (eg dialkyl esters thereof) and ethylene glycol and / or butane-1,4-diol, and mixtures of these polyalkylene terephthalates.
[0152] Preferred mixtures of aromatic polyalkylene terephthalates comprise 1 to 50% by weight, preferably 1 to 30% by weight, of polyethylene terephthalate and 50 to 99% by weight, preferably 70 to 99% by weight, of polybutylene terephthalate.
[0153] Aromatic polyalkylene terephthalates preferably used have viscosity values of 0.4 to 1.5 dl / g, preferably 0.5 to 1.2 dl / g, measured in an Ubbelohde viscometer in phenol / o-dichlorobenzene (1:1 parts by weight) at 25° C. at a concentration of 0.05 g / ml to ISO 307.
[0154] The aromatic polyalkylene terephthalates can be prepared by known methods (see, for example, Kunststoff-Handbuch, Vol. VIII, p. 695 ff., Carl-Hanser-Verlag, München 1973).
[0155] The most preferably used component B is a copolymer of styrene and acrylonitrile (SAN), an ABS copolymer or a mixture containing ABS and / or SAN, optionally in combination with other rubber-modified vinyl (co)polymers, preferably in combination with a graft polymer having a core-shell structure.
[0156] Component C
[0157] As component C, the composition preferably comprises at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica, and combinations of the fillers mentioned. Preferred compositions comprise talc as a component of component C. In particularly preferred compositions, in addition to inorganic pigments optionally used for coloring, only talc is used as component C.
[0158] Suitable quartz compounds include, for example, those formed by more than 97% of silicon dioxide (quartz), and the particle shape thereof is spherical and / or approximately spherical.
[0159] In a preferred embodiment, quartz with a coating containing a silicon-containing organic compound is used, wherein epoxysilane, methylsiloxane and / or methacrylsilane sizings are preferably used. Epoxysilane sizings are particularly preferred. The sizing of the inorganic filler can be carried out according to the general methods known to those skilled in the art.
[0160] The preferred quartz compound is finely divided (amorphous) fused quartz powder, which is made from electrically fused silica by iron-free grinding followed by air sieving. Quartz powder made from treated quartz sand can also be used.
[0161] Commercially available fused silica powders include, for example, Amosil from Quarzwerke GmbH (Germany). TM FW600 or Amosil TM FW600. Commercially available quartz powders include, for example, Sikron from Quarzwerke GmbH (Germany). TM SF300、Sikron TM SF600、Sikron TM SF800、Silbond TM SF600 EST or Mikro-Dorsilit from QUARZSANDE GmbH (Austria) TM 120.
[0162] Preferred inorganic fillers are talc-based mineral fillers. In the present invention, talc-based mineral fillers that come into consideration include all fillers that the person skilled in the art considers to be associated with talc or talcum powder. All commercially available fillers whose product descriptions contain the term talc or talcum powder as a characteristic feature are also suitable. In the present invention, talc-based mineral fillers are also referred to as talc for short.
[0163] Mixtures of various mineral fillers based on talc may also be used.
[0164] According to the invention, preference is given to mineral fillers having a talc content in accordance with DIN 55920 (2006 edition) of more than 80% by weight, preferably more than 95% by weight, particularly preferably more than 98% by weight, based on the total mass of the filler.
[0165] Talc is understood to be naturally occurring or synthetically produced talc. Pure talc is a silicate with a layered structure.
[0166] The talc types used as component C are preferably characterized by particularly high purity, characterized by an MgO content of 28% to 35% by weight, preferably 30% to 33% by weight, particularly preferably 30.5% to 32% by weight and an SiO2 content of 55% to 65% by weight, preferably 58% to 64% by weight, particularly preferably 60% to 62.5% by weight. Particularly preferred talc types are also characterized by an Al2O3 content of less than 5% by weight, more preferably less than 1% by weight, in particular less than 0.7% by weight.
[0167] It is also advantageous and therefore preferred to use the talc according to the invention in particular in the form of a finely ground type, wherein the median particle size d50 It is 0.2 to 10 μm, preferably 0.5 to 5 μm, more preferably 0.7 to 2.5 μm, and particularly preferably 1.0 to 2.0 μm.
[0168] Median particle size d 50 The diameter above and below which 50% by weight of the particles exist. 50 A mixture of talc types.
[0169] The talc types used according to the invention preferably have an upper particle size or crystallite size d of less than 50 μm, preferably less than 10 μm, particularly preferably less than 6 μm and especially preferably less than 2.5 μm. 97 .
[0170] Unless otherwise stated, the d of component C 97 and d 50 The values were determined by sedimentation analysis using a Sedigraph 5100 (Micromeritics GmbH, Erftstrasse 43, 41238 Germany) was measured according to ISO 13317-1 and ISO 13317-3 (2000 edition).
[0171] The talc may be surface treated, e.g. silanized, to ensure better compatibility with the polymer. For example, the talc may be modified with an adhesion promoter system based on functionalized silanes.
[0172] The use of compacted talc is also advantageous with regard to the processing and production of molding compounds.
[0173] Due to processing into molding compounds or moldings, the talc used may have a smaller d in the molding compound or molding than in the form originally used. 97 or 50 value.
[0174] As component B it is also possible to use kaolin, preferably surface-treated calcined kaolin.
[0175] The main component of naturally occurring kaolin is kaolinite, Al2(OH)4[Si2O5], and the minor components are feldspar, mica and quartz. In addition to this composition, kaolin containing nacrite, dickite, halloysite and hydrated halloysite in place of kaolinite or in addition to kaolinite can also be used.
[0176] The calcined kaolin of the present invention is obtained by heat-treating kaolin at at least 500° C., preferably 850° C. to 1100° C. Hydroxyl groups forming part of the crystal structure of kaolin are lost during the heat treatment, and kaolin is converted into calcined kaolin.
[0177] According to the invention, wollastonites can also be used. These wollastonites preferably have a carbon content of more than 0.1% by weight, preferably 0.2% to 2% by weight, particularly preferably 0.3% to 1% by weight, very particularly preferably 0.3% to 0.6% by weight, based on the wollastonite, as determined by elemental analysis. Such wollastonites are commercially available, for example under the trade name Nyglos® TM Available from NYCO Minerals Inc. Willsboro, NY, USA, where the model name is Nyglos TM 4-10992 or Nyglos TM 5-10992.
[0178] Preferred wollastonites have an average aspect ratio (ie the ratio of average fiber length to average fiber diameter) >6, in particular ≥7, and an average fiber diameter of 1 to 15 μm, preferably 2 to 10 μm, in particular 4 to 8 μm.
[0179] Another suitable filler is calcium carbonate CaCO3. Calcium carbonate occurs naturally in the form of minerals such as calcite, aragonite and vaterite and is also the main component of limestone, chalk and marble. Calcium carbonate can also be produced synthetically, which may be advantageous due to its higher purity. Preferably, a median particle size d 50 Calcium carbonate with a particle size of 0.1 to 5 μm.
[0180] Another suitable filler is aluminum hydroxide Al(OH)3. Aluminum hydroxide occurs naturally in mineral form, for example gibbsite, bayerite and nordstromite. Aluminum hydroxide can also be produced by synthetic methods, which may be advantageous due to its higher purity. Preferably, a median particle size d 50 Calcium carbonate of 1 to 5 μm.
[0181] Another suitable filler is mica, preferably metal oxide-coated mica. The mica may be naturally occurring mica or synthetically produced mica, the latter being preferred due to its generally higher purity. Micas obtained from nature are usually accompanied by other minerals. In the case of mica obtained from nature, component B "mica" also contains the relevant impurities in the amounts indicated. The mica is preferably based on muscovite, i.e. it preferably contains at least 60% by weight, more preferably at least 70% by weight, more preferably at least 85% by weight, particularly preferably at least 90% by weight of muscovite, based on the total weight of the mica portion.
[0182] The metal oxide coating preferably comprises one or more coatings containing titanium dioxide, tin oxide, aluminum oxide and / or iron oxide, wherein the metal oxide is more preferably iron (III) oxide (Fe2O3), iron (II, III) oxide (Fe3O4, a mixture of Fe2O3 and FeO) and / or titanium dioxide, particularly preferably titanium dioxide.
[0183] The median particle size (d 50 ) is preferably 1 to 100 μm, more preferably 5 to 80 μm for synthetic mica, more preferably 3 to 30 μm for natural mica, generally 3.5 to 15 μm for mica, very particularly preferably 4.0 to 10 μm, most preferably 4.5 to 8.0 μm.
[0184] Suitable micas available on the market include, for example, the product group Tremica from HPF Minerals (Quarzwerke Gruppe, Germany). TM products.
[0185] As component C, it is also possible with preference to use one or more pigments based on titanium dioxide, optionally in combination with other inorganic pigments, such as iron oxide, aquamarine, ultramarine, zinc white and zinc oxide.
[0186] This is a naturally occurring, synthetically produced or modified naturally occurring pigment or a mixture thereof. The titanium dioxide pigment preferably has a crystal structure modification selected from rutile, anatase or brookite. The preferred modification is rutile.
[0187] The density of the pigments according to the invention based on titanium dioxide (according to DIN EN ISO 787-10) is 3.8 to 4.0 g / cm 3 , preferably 3.8 to 4.3 g / cm 3 , particularly preferably 4.0 to 4.2 g / cm 3 .
[0188] The pigment can be obtained in a known manner by the sulfate process or the chloride process from natural raw materials, for example ilmenite, rutile ore or TiO2 slag.
[0189] The pigments may have an inorganic and / or organic surface modification, preferably based on aluminum and / or silicone compounds. The proportion of titanium dioxide (according to DIN EN ISO 591) is preferably >90% by weight, particularly preferably >92% by weight, more preferably >95% by weight.
[0190] In a preferred embodiment, the oil absorption of the pigment (according to ISO 787-5) is 5 to 50 g / 100 g pigment, more preferably 10 to 25 g / 100 g pigment, particularly preferably 12 to 18 g / 100 g pigment.
[0191] Component D
[0192] As component D, the composition may contain one or more non-polymeric polymer additives and / or non-polymeric processing aids different from component C, which are preferably selected from flame retardants, anti-drip agents, flame retardant synergists, smoke suppressants, lubricants and release agents, nucleating agents, antistatic agents, conductive additives, stabilizers (for example hydrolysis, heat aging and UV stabilizers and transesterification inhibitors), flow promoters, phase compatibilizers, organic fillers and reinforcing agents and organic dyes and pigments.
[0193] In a preferred embodiment, fatty acid esters, particularly preferably fatty acid esters of pentaerythritol or glycerol, are used as lubricants and mold release agents.
[0194] In a preferred embodiment, at least one representative selected from the group consisting of sterically hindered phenols, organic phosphites and sulfur-based costabilizers is used as stabilizer.
[0195] In a particularly preferred embodiment, at least one representative from the group consisting of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl) phosphite is used as stabilizer.
[0196] Method for producing molding compound
[0197] In the process according to the invention, thermoplastic molding materials having a low mass content of free BPA are produced from components A, B and C and optionally D according to the invention.
[0198] The term "molding compound" is understood to mean the product obtained when the ingredients of the composition are melt compounded and melt extruded.
[0199] The present invention also provides a corresponding method for producing the molding compound according to the invention as described above.
[0200] The molding materials of the present invention can be used to produce various types of moldings. These moldings can be produced, for example, by injection molding, extrusion and blow molding. Another form of processing is to produce moldings from previously produced sheets or films by deep drawing.
[0201] Examples of such moldings are films, profiles, various types of housing parts, for example housing parts for household appliances such as juicers, coffee machines, blenders, etc.; housing parts for office machines such as displays, flat-panel displays, notebook computers, printers, copiers, etc.; panels, pipes, electrical installation pipes, windows, doors and other profiles for the construction sector (interior decoration and exterior applications), as well as electrical and electronic components, such as switches, plugs and sockets, and parts for commercial vehicles (especially in the automotive sector). The compositions and molding materials of the invention are also suitable for producing the following moldings or moldings: interior assembly parts for rail vehicles, ships, aircraft, buses and other motor vehicles, body parts for motor vehicles, housings for electrical equipment containing small transformers, housings for information processing and transmission equipment, housings and facings for medical equipment, massage equipment and their housings, children's toy cars, sheet wall elements, housings for safety equipment, insulated transport containers, moldings for sanitary and bathing equipment, protective grilles for ventilation openings and housings for garden equipment.
[0202] The following embodiments are particularly preferred:
[0203] 1. Thermoplastic molding compound containing
[0204] A) at least one polycarbonate and / or polyester carbonate, each of which contains structural units derived from bisphenol A,
[0205] B) other polymers different from component A or a mixture consisting of polymers each different from component A,
[0206] Component B consists of the following
[0207] B 1) at least one thermoplastic polymer and
[0208] Optionally B2) at least one non-thermoplastic polymer,
[0209] C) at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica and combinations of said fillers, and
[0210] D) optionally at least one non-polymeric polymer additive and / or at least one non-polymeric processing aid, each of which is different from component C,
[0211] wherein the weight ratio of component B to component C is at least 0.5,
[0212] and wherein the weight proportion of component B1 in component B is at least 20%,
[0213] And the mass proportion of free bisphenol A in the molding material is less than 30 ppm.
[0214] 2. The molding compound according to embodiment 1, wherein the weight ratio of component B to component C is at least 1.
[0215] 3. The molding compound according to embodiment 1, wherein the weight ratio of component B to component C is at least 1.3.
[0216] 4. The molding compound according to any one of the preceding embodiments, comprising
[0217] 30 to 85% by weight of component A,
[0218] 2 to 50% by weight of component B,
[0219] 3 to 40% by weight of component C,
[0220] 0 to 10% by weight of component D.
[0221] 5. The molding compound according to any one of the preceding embodiments, comprising
[0222] 40 to 80% by weight of component A,
[0223] 7 to 40% by weight of component B,
[0224] 5 to 30% by weight of component C,
[0225] 0.1 to 5% by weight of component D.
[0226] 6. The molding compound according to any one of the preceding embodiments, comprising
[0227] 45 to 75% by weight of component A,
[0228] 15 to 35% by weight of component B,
[0229] 8 to 25% by weight of component C,
[0230] 0.2 to 3% by weight of component D. .
[0231] 7. The molding compound according to any one of the preceding embodiments, wherein the weight ratio of component B to component C is 0.5 to 5.
[0232] 8. The molding compound according to any one of the preceding embodiments, wherein the weight ratio of component B to component C is 1 to 3.
[0233] 9. The molding compound according to any one of the preceding embodiments, wherein the weight ratio of component B to component C is from 1.3 to 2.
[0234] 10. The molding compound according to any of the preceding embodiments, wherein component C contains talc.
[0235] 11. A molding compound according to any of the preceding embodiments, wherein component B is selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more such polymers in each case.
[0236] 12. A molding compound according to any one of the preceding embodiments, wherein component B is selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, and mixtures of one or more of these polymers.
[0237] 13. The molding compound according to any one of the preceding embodiments, wherein the mass proportion of free bisphenol A is less than 20 ppm.
[0238] 14. The molding compound according to any one of the preceding embodiments, wherein the mass proportion of free bisphenol A is less than 10 ppm.
[0239] 15. The molding compound according to any of the preceding embodiments, wherein the proportion by weight of component B1 in component B is at least 50%.
[0240] 16. The molding compound according to any of the preceding embodiments, wherein the proportion by weight of component B1 in component B is at least 70%.
[0241] 17. The molding compound according to any of the preceding embodiments, wherein component A contains at least 20% by weight of structural units derived from bisphenol A, based on the sum of all structural units derived from bisphenols.
[0242] 18. The molding compound according to any of the preceding embodiments, wherein component A contains 100% by weight of structural units derived from bisphenol A, based on the sum of all structural units derived from bisphenol.
[0243] 19. The molding compound according to any one of the preceding embodiments, consisting of components A, B, C and D.
[0244] 20. A method for producing a thermoplastic molding compound, comprising the following steps
[0245] (i) The masterbatch is produced by melt compounding the following components in an internal kneader or a co-kneader:
[0246] B) a polymer other than a polycarbonate containing structural units derived from bisphenol A and other than a polyester carbonate containing structural units derived from bisphenol A, or a mixture of polymers other than a polycarbonate containing structural units derived from bisphenol A and other than a polyester carbonate containing structural units derived from bisphenol A,
[0247] Component B consists of the following
[0248] B1) at least one thermoplastic polymer and
[0249] optionally B2) at least one non-thermoplastic polymer,
[0250] C) at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica and combinations of said fillers, and
[0251] D) optionally a non-polymeric polymer additive and / or at least one non-polymeric processing aid, each of which is different from component C,
[0252] wherein the weight ratio of component B to component C is at least 0.5,
[0253] and
[0254] The weight proportion of component B1 in component B is at least 50%,
[0255] (ii) melt compounding the masterbatch obtained in step (i) with at least one polycarbonate and / or polyester carbonate as component A and optionally further proportions of components B, C and / or D and / or the total amount of component D, the polycarbonate and / or polyester carbonate each containing structural units derived from bisphenol A.
[0256] 21. A method according to embodiment 20, wherein component B is selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more of each of these polymers.
[0257] 22. A method according to embodiment 20, wherein component B is selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, and mixtures of one or more of each of these polymers.
[0258] 23. The method according to any one of embodiments 20 to 22, wherein the weight ratio of component B to component C is at least 1.
[0259] 24. The method according to any one of embodiments 20 to 22, wherein the weight ratio of component B to component C is 0.5 to 5.
[0260] 25. The method according to any one of embodiments 20 to 22, wherein the weight ratio of component B to component C is 1.3 to 2.
[0261] 26. The method according to any one of the preceding embodiments 20 to 25, wherein the weight proportion of component B1 in component B is at least 60%.
[0262] 27. The method according to any one of the preceding embodiments 20 to 25, wherein the weight proportion of component B1 in component B is at least 70%.
[0263] 28. The method according to any one of the preceding embodiments 20 to 27, wherein component C contains talc.
[0264] 29. The method according to any one of the preceding embodiments 20 to 28, wherein at least 80% by weight of the total amount of component C is used in step (i).
[0265] 30. The method according to any one of the preceding embodiments 20 to 29, wherein the total amount of component C is used in step (i).
[0266] 31. The method according to any of the preceding embodiments 20 to 30, wherein step (ii) is carried out in a compounding device selected from a single-shaft extruder, a co-rotating or counter-rotating twin-screw extruder, a planetary roll extruder, an internal kneader and a co-kneader.
[0267] 32. The method according to any one of embodiments 20 to 31, wherein steps (i) and (ii) are carried out in a temperature range of 200°C to 350°C, wherein the residence time of the components in melt form is 15 seconds to 5 minutes.
[0268] 33. The process according to any one of the preceding embodiments 20 to 32, wherein step (i) is carried out in a co-kneader.
[0269] 34. The method according to any one of the preceding embodiments 20 to 33, wherein step (ii) is carried out in a twin-screw extruder.
[0270] 35. The method according to embodiment 33, wherein step (i) is carried out at a melt temperature of 210°C to 260°C.
[0271] 36. The method according to embodiment 34, wherein step (ii) is carried out at a melt temperature of 260°C to 320°C.
[0272] 37. The method according to any one of embodiments 33 or 35, wherein the residence time of the components in melt form in step (i) is from 1 to 5 minutes.
[0273] 38. The method according to any one of embodiments 33 or 35, wherein the residence time of the components in melt form in step (i) is from 2 to 3.5 minutes.
[0274] 39. The method according to any one of embodiments 34 or 36, wherein the residence time of the components in melt form in step (ii) is from 15 to 60 seconds.
[0275] 40. The method according to any one of the preceding embodiments 20 to 30,
[0276] wherein step (i) is carried out in a co-kneader at a melt temperature of 210° C. to 260° C. and with a residence time of the components in melt form of 1 to 5 minutes, and
[0277] Step (ii) is carried out in a twin-screw extruder at a melt temperature of 260° C. to 320° C. and with a residence time of the components in melt form of 15 to 60 seconds.
[0278] 41. Use of the thermoplastic molding material according to any of embodiments 1 to 19 for producing moldings.
[0279] 42. A molding comprising or consisting of the molding compound according to any one of embodiments 1 to 19.
[0280] 43. A molding comprising or consisting of a molding compound produced according to any one of embodiments 20 to 40.
[0281] The present invention will now be more specifically described with reference to the following examples, but the present invention is not limited thereto. Example
[0282] Component A-1:
[0283] The linear polycarbonate based on bisphenol A produced by the phase interface polymerization method has a weight average molecular weight Mw of 28000 g / mol (determined by GPC in dichloromethane at room temperature against BPA-PC standards).
[0284] Component A-2:
[0285] The linear polycarbonate based on bisphenol A produced by the phase interface polymerization method has a weight average molecular weight Mw of 25000 g / mol (determined by GPC in dichloromethane at room temperature against BPA-PC standards).
[0286] Component B-1:
[0287] A thermoplastic acrylonitrile (A)-butadiene (B)-styrene (S)-n-butyl acrylate (BA) polymer produced by a bulk polymerization process, which contains a dispersed phase consisting of rubber particles based on pure polybutadiene rubber as a grafting base grafted with styrene-acrylonitrile-n-butyl acrylate copolymer (which contains styrene-acrylonitrile-n-butyl acrylate copolymer content) and a styrene-acrylonitrile-n-butyl acrylate copolymer matrix not bonded to the rubber. The A:B:S:BA ratio of component B-1 is 22.5:10:63:4.5% by weight, and the gel content (determined as the proportion insoluble in acetone) is 19% by weight. The weight average molecular weight M of the styrene-acrylonitrile-n-butyl acrylate copolymer soluble in tetrahydrofuran in component B-1 is w (measured by GPC with tetrahydrofuran as solvent and polystyrene standard) is 115 kg / mol. The median particle size D50 of the dispersed phase measured by ultracentrifugation is 0.5 μm. The melt flow rate (MFR) of component B-1 is 28 g / 10 min measured at 220° C. under a piston load of 10 kg according to ISO 1133 (2012 edition).
[0288] Component B-2:
[0289] A non-thermoplastic graft polymer with a core-shell structure prepared by emulsion polymerization, which consists of 75% by weight of a silicone-acrylate composite rubber core and 25% by weight of a polymethyl methacrylate shell. The gel content of component B-2 measured in acetone at room temperature is 90% by weight (Metablen TM S-2030, manufacturer: Mitsubishi Chemical, Japan).
[0290] Component B-3:
[0291] A thermoplastic SAN copolymer having an acrylonitrile content of 28 wt % and a weight average molecular weight of about 130,000 g / mol (determined by GPC in tetrahydrofuran at room temperature using polystyrene standards).
[0292] Component B-4:
[0293] A thermoplastic SAN copolymer having an acrylonitrile content of 23% by weight and a weight average molecular weight of about 100,000 g / mol (determined by GPC in tetrahydrofuran at room temperature using polystyrene standards).
[0294] Component B-5
[0295] Polyethylene terephthalate (e.g. PET from Invista, Germany) has an intrinsic viscosity of 0.623 dl / g. The specific viscosity is measured at 25° C. in dichloroacetic acid at a concentration of 1%. The intrinsic viscosity is calculated from the specific viscosity according to the following formula:
[0296] Intrinsic viscosity = specific viscosity x 0.0006907 + 0.063096
[0297] Component C:
[0298] Compacted talc, with an iron oxide content of 0.2 wt.%, an aluminum oxide content of 0.4 wt.%, a calcium oxide content of 0.3 wt.%, d 50 (Sedimentation analysis) 1.1μm; Type: 3CA, manufacturer: Imerys Performance Additives (Paris, France).
[0299] Component D-1:
[0300] Pentaerythritol tetrastearate, Loxiol TM P 861 / 3.5 Special (Emery Oleochemicals GmbH, Düsseldorf, Germany).
[0301] Component D-2:
[0302] Irganox TM B900 (80% Irgafos TM 168 (tris(2,4-di-tert-butylphenyl) phosphite) and 20% Irganox TM 1076 (mixture of 2,6-di-tert-butyl-4-(octadecyloxycarbonylethyl)phenol); BASF (Ludwigshafen, Germany).
[0303] Component D-3:
[0304] Fabutit TM 289: Orthophosphoric acid adsorbed on silica gel (Chemische Fabrik Budenheim KG, Germany).
[0305] Component D-4:
[0306] Black Pearls TM 800: Carbon black (Cabot Corp., USA)
[0307] Component D-5
[0308] Solid phosphorous acid H3PO3, Sigma-Aldrich Chemie GmbH, Germany
[0309] Component D-6
[0310] Irganox TM 1010 (pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxyhydrocinnamate); BASF (Ludwigshafen, Germany)
[0311] Component D-7
[0312] Dimer phosphite, 1,1-biphenyl-4,4′-diyldiphosphite tetrakis(2,4-di-tert-butylphenyl)ester, Hostanox TM P-EPQ, Clariant (Muttenz, Switzerland)
[0313] Component D-8
[0314] A- 907P (Honeywell International Inc., Morristown, USA): propylene-maleic anhydride copolymer, saponification value of 90 mg KOH / g, viscosity at 190°C of 350 cps.
[0315] Production of molding compounds
[0316] Comparative Example 1:
[0317] Clextral SAS (France) In a 32HT twin-screw extruder, components A to D-4 are processed into molding compounds in a single compounding step in the weight proportions shown in Table 1 at a material temperature of about 315° C. measured in the melt at the extruder nozzle outlet and under a negative pressure of 100 mbar (absolute). All components of the composition, except talc, are metered together into the inlet of the extruder through the main feed opening and melted and dispersed with each other by the introduction of thermal and mechanical energy. The talc is metered into the melt mixture of the remaining components through a side extruder, i.e., metered into the extruder zone located on the other side of the melting zone relative to the main feed opening. In the process, the residence time of the components in melt form is about 30 seconds.
[0318] Comparative Example 2:
[0319] The production of the molding compound takes place in two process steps, both of which are carried out at the Clextral 32HT twin-screw extruder. In the first method step, the total amount of components A and D-3 is processed into an acid-stabilized polycarbonate pre-compound according to the weight ratio shown in Table 1 at a material temperature of about 315° C. measured in the melt at the extruder nozzle outlet and a negative pressure of 100 mbar (absolute) is applied. In this first method step, the residence time of the components in the form of a melt is about 30 seconds. In the second method step, the acid-stabilized polycarbonate pre-compound obtained in step 1 is processed into a molding compound in the same twin-screw extruder at the same temperature, residence time and vacuum conditions according to the dosage ratio shown therein. Talc is metered into the melting zone through a side extruder. All other components (including the acid-stabilized polycarbonate pre-compound) are introduced into the extruder together through the main feed port, melted and dispersed with each other, and then the talc is supplied through the side extruder.
[0320] Embodiment 3 of the present invention:
[0321] The production of the molding compound is carried out in two process steps. In the first process step, the components B-1, B-2, B-3 and C are mixed with one another in the weight proportions shown in Table 1 in an MX58 co-kneader from Buss AG (Switzerland), more precisely at a temperature of about 230° C. in the melt measured with a thermocouple located at the end of the extruder, immediately upstream of the nozzle plate. Under these conditions, the thermoplastic components B-1 and B-3 are in the form of a melt, i.e., the components B-2 and C are dispersed in the melt mixture of the components B-1 and B3 in this process step, wherein a molten thermoplastic mass consisting of the intimately mixed components B-1, B-2, B-3 and C is formed in the kneader. The residence time of the molten mass in the kneader in this process step is about 3 minutes. This process step is carried out at atmospheric pressure, i.e., no degassing vacuum is applied. As a result of the first process step, a talc masterbatch is obtained. In the second process step, the talc masterbatch obtained in step 1 was prepared together with the other ingredients shown in Table 1 in a Clextral SAS (France) The molding compound was processed in a 32HT twin-screw extruder at a material temperature of about 315° C. measured in the melt at the extruder nozzle outlet and under an applied negative pressure of 100 mbar (absolute). In this second process step, the residence time of the components in melt form was about 30 seconds. All components of the composition, including the talc masterbatch produced in the previous process step, were metered together through the main feed opening into the inlet of the extruder and melted by the introduction of thermal and mechanical energy and subsequently dispersed with one another in the extruder.
[0322] Comparative Example 4:
[0323] As in Comparative Example 1, a Clextral SAS (France) The production was carried out in a single compounding step in a 32HT twin-screw extruder. Component B-4 was used instead of component B-3.
[0324] Embodiment 5 of the present invention:
[0325] As in Example 3 according to the invention, the production was carried out in two process steps, wherein again the first process step was carried out in a co-kneader of the type MX58 from Buss AG (Switzerland) and the second process step in a Clextral SAS (France). The extruder was carried out in a 32HT twin-screw extruder. Component B-4 was used instead of component B-3.
[0326] Comparative Example 6:
[0327] The production of the molding compound takes place in two process steps, both of which are carried out in the Clextral 32HT twin-screw extruder. In the first method step, the components B-1, B-2, B-4 and C are processed in the weight proportions shown in Table 1 at a material temperature of about 300° C. measured in the melt at the outlet of the extruder nozzle and a negative pressure of 100 mbar (absolute). Under these conditions, the thermoplastic components B-1 and B-4 are in the form of a melt, i.e., components B-2 and C are dispersed in the melt mixture of components B-1 and B4 in this method step, wherein a molten thermoplastic material consisting of intimately mixed components B-1, B-2, B-4 and C is formed in the extruder. In the first method step, the residence time of the components in the melt is about 30 seconds. The result of the first method step is to obtain a talc masterbatch. In the second method step, the talc masterbatch is obtained in the Clextral SAS (France) company mentioned above. The talc masterbatch obtained in step 1 was processed into a molding compound together with the other ingredients shown in Table 1 in a twin-screw extruder of the 32HT type at a mass temperature of about 315° C. measured in the melt at the extruder nozzle outlet and under an applied negative pressure of 100 mbar (absolute). In this second process step, the residence time of the components in melt form was about 30 seconds. All components of the composition, including the talc masterbatch produced in the previous process step, were metered together into the inlet of the extruder through the main feed opening and melted by the introduction of thermal and mechanical energy and subsequently dispersed with one another in the extruder.
[0328] Comparative Example 7:
[0329] As in Comparative Example 1, a Clextral SAS (France) The production was carried out in a single compounding step in a 32HT twin-screw extruder. The ingredients shown in Table 1 for Comparative Example 7 were used. The melt temperature at the extruder nozzle outlet was about 305°C.
[0330] Embodiment 8 of the present invention
[0331] As in Example 3 according to the invention, the production was carried out in two process steps, wherein again the first process step was carried out in a co-kneader of the type MX58 from Buss AG (Switzerland) and the second process step was carried out in a Clextral SAS (France). The preparation was carried out in a 32 HT twin-screw extruder. The ingredients shown in Table 1 for Example 8 were used. In the first method step, the total amount of components B-5, C and D-8 was processed into a masterbatch. In the second method step, the masterbatch was mixed and compounded with the remaining components. In the first method step, the melt temperature at the nozzle outlet of the compounding device was about 260° C. and in the second method step was about 305° C.
[0332] Determination of free bisphenol A content in compounded products
[0333] To determine the content of free bisphenol A (abbreviated [BPA]), a sample of the prepared pellets was dissolved in dichloromethane and reprecipitated with acetone. The precipitated compound portion was filtered out and the filtrate was analyzed by high pressure liquid chromatography (HPLC-UV) with a UV detector using an external standard method. A C18 phase was used as column material and a gradient of water and methanol was used as eluent.
[0334] Production and testing of molded parts
[0335] In order to evaluate the material ductility under multiaxial stress, 10 specimens of Examples V4, 5 and V6 with a size of 60 mm x 60 mm x 2 mm were subjected to a puncture test at 23 ° C according to ISO 6603-2 (2002 edition). The maximum force and the total energy were measured. The percentage of brittle fractures was used as a measure of the material ductility under multiaxial stress. Brittle fracture is understood to be a fracture failure in which some parts of the specimen broke apart during the puncture test.
[0336] The test specimens for the puncture tests were produced in an Arburg 270E injection molding machine at a material temperature of 260° C. and a mold temperature of 80° C. by means of an injection speed of 40 mm / s.
[0337]
[0338] The data in Table 1 show that the free bisphenol A content in the pellets of Example 3 prepared using the process of the present invention is significantly lower than that of Comparative Examples V1 and V2 prepared using other processes. Unfavorably high levels of free bisphenol A are obtained both in the case of mixing all components in a single step (V1) and in the alternative two-step compounding process (V2) in which an acid-stabilized polycarbonate precompound is first prepared from components A and D-3 in a twin-screw extruder.
[0339] Comparative Example 4 shows again that high contents of free bisphenol A are obtained by means of a process with only one compounding step. It can be seen from inventive example 5 and comparative example 6 that low contents of free bisphenol A can only be achieved using the process according to the invention. If the first process step is carried out in a twin-screw extruder, the content of free bisphenol A is many times higher.
[0340] Information about the material ductility of the molding compounds is also disclosed in Examples V4, 5 and V6. The inventive molding compound in Example 5 exhibits a higher maximum force and a higher total energy in the puncture test than the comparative examples V4 and V6. In particular, however, unlike V4 and V6, no brittle fracture (fracture failure) occurs in Example 5.
[0341] Comparative Example V7 and Example 8 according to the invention show that the content of free bisphenol A is also reduced when polyesters are used as component B in the process according to the invention.
Claims
1. Thermoplastic molding compound containing A) at least one polycarbonate and / or polyester carbonate, each of which contains structural units derived from bisphenol A, B) other polymers different from component A or a mixture consisting of polymers each different from component A, Component B consists of the following B1) at least one thermoplastic polymer and Optionally B2) at least one non-thermoplastic polymer, C) at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica and combinations of said fillers, and D) optionally at least one non-polymeric polymer additive and / or at least one non-polymeric processing aid, each of which is different from component C, wherein the weight ratio of component B to component C is at least 0.5, and wherein the weight proportion of component B1 in component B is at least 20%, And the mass proportion of free bisphenol A in the molding material is less than 30 ppm.
2. The molding compound according to claim 1, comprising 30 to 85% by weight of component A, 2 to 50% by weight of component B, 3 to 40% by weight of component C, 0 to 10% by weight of component D. 3 . The molding compound according to claim 1 , wherein the weight ratio of component B to component C is from 0.5 to 5. 4 . 4 . The molding compound according to claim 1 , wherein component C contains talc.
5. The molding compound according to any of the preceding claims, wherein component B is selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more of these polymers in each case. 6 . The molding compound according to claim 1 , wherein component A comprises at least 20% by weight of structural units derived from bisphenol A, based on the sum of all structural units derived from bisphenols.
7. A method for producing a thermoplastic molding compound, comprising the following steps (i) The masterbatch is produced by melt compounding the following components in an internal kneader or a co-kneader: B) a polymer other than a polycarbonate containing structural units derived from bisphenol A and other than a polyester carbonate containing structural units derived from bisphenol A, or a mixture of polymers other than a polycarbonate containing structural units derived from bisphenol A and other than a polyester carbonate containing structural units derived from bisphenol A, Component B consists of the following B1) at least one thermoplastic polymer and optionally B2) at least one non-thermoplastic polymer, C) at least one inorganic filler selected from quartz compounds, talc, wollastonite, kaolin, CaCO3, titanium dioxide and titanium dioxide in combination with other inorganic pigments, Al(OH)3, AlO(OH), Mg(OH)2 and mica and combinations of said fillers, and D) optionally a non-polymeric polymer additive and / or at least one non-polymeric processing aid, each of which is different from component C, wherein the weight ratio of component B to component C is at least 0.5, and The weight proportion of component B1 in component B is at least 50%, (ii) melt compounding the masterbatch obtained in step (i) with at least one polycarbonate and / or polyester carbonate as component A and optionally further proportions of components B, C and / or D and / or the total amount of component D, the polycarbonate and / or polyester carbonate each containing structural units derived from bisphenol A.
8. The method according to claim 7, wherein component C contains talc.
9. The method according to any one of claims 7 or 8, wherein component B is selected from rubber-free vinyl (co)polymers, rubber-modified vinyl (co)polymers, aromatic polyesters and mixtures of one or more of these polymers in each case.
10. The process according to any one of claims 7 to 9, wherein step (ii) is carried out in a compounding device selected from a single-screw extruder, a co-rotating or counter-rotating twin-screw extruder, a planetary roll extruder, an internal kneader and a co-kneader.
11. The process according to any one of claims 7 to 10, wherein step (i) is carried out in a co-kneader.
12. The process according to any one of claims 7 to 11, wherein step (ii) is carried out in a twin screw extruder.
13. The process according to any one of claims 7 to 9, wherein step (i) is carried out in a co-kneader at a melt temperature of 210°C to 260°C, and step (ii) is carried out in a twin-screw extruder at a melt temperature of 260°C to 320°C.
14. The process according to any one of the preceding claims 7 to 9 or 13, wherein step (i) is carried out in the co-kneader with a residence time of the components in the melt of 1 to 5 minutes, and step (ii) is carried out in the twin-screw extruder with a residence time of the components in the melt of 15 to 60 seconds.
15. A molded article comprising or consisting of the molding compound according to any one of claims 1 to 6, or comprising or consisting of a molding compound produced by the method according to any one of claims 7 to 14.
Citation Information
Patent Citations
modified aromatic polyesters for injection molding
DE1900270A1
DE2035390A1
Continuous condensn of polyarylesters - suitable for extrusion or casting into films
DE2232877A1
reinforced intergranular thermoplastic polyester compositions
DE2248242A1
MOBILE DEVICE FOR GRINDING AND CLEANING FLOORS
DE2407674A1